2010
DOI: 10.1002/cjoc.201090037
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Promoted and Ionic Liquid Catalyzed Cyclocondensation Reaction for the Synthesis of 4(3H)‐Quinazolinones

Abstract: 4(3H)-Quinazolinones were synthesized in high yields by one-pot three-component condensation of anthranilic acid, carboxylic acid and aniline in the presence of ionic liquid such as 1-n-butyl-3-methylimidazolium tetrafluoroborate (BMImBF 4 ) as catalyst under solvent free and neutral conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…233 In the presence of [BMIm]BF 4 , one-pot three-component condensation of anthranilic acid, carboxylic acid and aniline proceeded well with the aid of ultrasound irradiation, providing 4(3H)-quinazolinones in high yields. 234 Ionic liquid [BMIm]PF 6 has been demonstrated by Xu et al 235 to be an efficient and recyclable medium for highly chemoselective synthesis of 2,2-dimethyl-6-substituted 4-piperidones 123 via a L-proline catalyzed four-component tandem Mannich reaction of ammonia, aldehydes and acetone (Scheme 69). The ionic liquid [BMIm]PF 6 not only serves as a reaction medium, but also significantly enhances the chemoselectivity.…”
Section: Mcrs In Ionic Liquidsmentioning
confidence: 99%
“…233 In the presence of [BMIm]BF 4 , one-pot three-component condensation of anthranilic acid, carboxylic acid and aniline proceeded well with the aid of ultrasound irradiation, providing 4(3H)-quinazolinones in high yields. 234 Ionic liquid [BMIm]PF 6 has been demonstrated by Xu et al 235 to be an efficient and recyclable medium for highly chemoselective synthesis of 2,2-dimethyl-6-substituted 4-piperidones 123 via a L-proline catalyzed four-component tandem Mannich reaction of ammonia, aldehydes and acetone (Scheme 69). The ionic liquid [BMIm]PF 6 not only serves as a reaction medium, but also significantly enhances the chemoselectivity.…”
Section: Mcrs In Ionic Liquidsmentioning
confidence: 99%
“…As a part of our ongoing program on the development of novel synthetic methods in organic synthesis under mild conditions, 36 we wish to report a simple and efficient method for the synthesis of quinoxalines in the presence of thiamine hydrochloride (VB 1 ) as an inexpensive, non-toxic and metal ion free catalyst at ambient temperature (scheme 1).…”
Section: Resultsmentioning
confidence: 99%
“…When this reaction was performed in the molecular solvent EtOH, the addition of NaOH and 30% H 2 O 2 under reflux for 1 h was necessary to obtain 75% yield of the product. 432 Pawar et al 433 reported the synthesis of 4(3H)-quinazolinones 312 promoted by [BMIM][BF 4 ] under ultrasound irradiation. The products 312 were achieved from the three-component condensation of anthranilic acid 91, primary aromatic amines 5, and carboxylic acid 56, with equimolar amounts of the reactants and IL (Scheme 97).…”
Section: Pyrimidines and Pyrimidinonesmentioning
confidence: 99%
“…Pawar et al reported the synthesis of 4­(3 H )-quinazolinones 312 promoted by [BMIM]­[BF 4 ] under ultrasound irradiation. The products 312 were achieved from the three-component condensation of anthranilic acid 91 , primary aromatic amines 5 , and carboxylic acid 56 , with equimolar amounts of the reactants and IL (Scheme ).…”
Section: Synthesis Of Six-membered Heterocyclesmentioning
confidence: 99%